인천 및 경기지역 성인 여성의 전자상거래에서 식품 구매실태와 식습관과의 관련성 - 박유진(Yu-Jin Park); 김미현(Mi-Hyun Kim); 최미경(Mi-Kyeong Choi) (Journal of nutrition and health, 2019)
Purpose: This study examined the food purchases from e-commerce and its relation to eating behaviors or habits in adult women in Incheon and Gyeonggi. Methods: A total of 410 subjects participated in the questionnaire survey. Food purchases in e-commerce and food habits were compared according to age, marital status, and food purchase status in e-commerce of the subjects. Results: Approximately 88% of the subjects had experience of buying foods by e-commerce; more than 40% of the subjects spent less than 100,000 Won buying foods by e-commerce in the past 6 months. The major purchases were coffee and tea, instant food and frozen food, and water and beverages. The reasons for buying foods in e-commerce were cheaper price, convenience of delivery, and variety of food choices. The main factors considered for purchasing foods in e-commerce were price and quality followed by rapid and accurate delivery, and food label and information. Approximately 70% of the subjects were very satisfied or satisfied with their food purchase in e-commerce, and 96% answered that they were willing to buy food in e-commerce again. The perception on the advantages of food purchases in e-commerce was 3.6 points out of 5 and significantly lower in the over 50s and married group. The subjects with experience and high cost of food purchase in e-commerce showed significantly low scores of dietary behaviors and eating habits, which is undesirable. Conclusion: A high percentage of people purchased foods by e-commerce, and they showed undesirable eating habits, especially when the cost of purchasing foods by e-commerce is high. These results showed that purchasing foods in e-commerce may be related to consumers' food habits. Therefore, continuous attention and nutrition guidance for e-commerce consumers are needed. 본 연구에서는 인천 및 경기지역에 거주하며 식품 구매의 주 소비자인 성인 여성 410명을 대상으로 전자상거래에서 식품 구매 실태를 파악하고 식품 구매 상태에 따른 식생활과의 관련성을 분석하여 향후 전자상거래를 통한 올바른 식품 구매 지도 및 확산을 위한 기초자료로 활용하고자 하였다. 조사대상자의 연령은 20 ~ 50대가 비교적 고르게 분포하였으며, 기혼자가 70.5%였다. 전자상거래 식품 구매경험자는 87.6%이었으며, 최근 6개월 이내 식품 구매액은 대상자의 43.2%가 10만원 미만이었다. 식품 쇼핑몰에 대한 정보는 20 ~ 40대는 인터넷 검색을 통해서, 50대 이상의 경우에는 TV 광고를 통해서 얻는 경우가 많았다. 전자상거래에서 주로 구매하는 식품은 커피, 티, 간편조리식품, 냉장, 냉동식품이 40% 이상으로 높았다. 전자상거래를 이용하여 식품을 구매하는 이유는 '오프라인 매장 보다 저렴해서' '배송 및 운반이 편리해서', '전자상거래에서 판매되고 있는 식품의 종류가 다양해서', '경제활동 및 육아로 식품을 직접 구입할 시간이 부족해서' 순이었다. 전자상거래 식품 구매 시 중요하게 생각하는 부분은 '가격 및 품질'이 44.8%로 가장 높았으며, '신속하고 정확한 배송', '제품의 유통기한, 내용량, 영양성분, 성분명 및 함량의 명확한 표기' 순이었다. 전자상거래에서 식품 구매 후 대상자의 69.1%가 매우 만족 또는 만족하였으며, 95.5%는 향후 전자상거래에서 식품 구매의사가 있다고 답하였다. 전자상거래에서 식품 구매의 장점과 단점에 대한 인식은 5점 만점에 각각 3.6점과 3.7점이었으며, 50대 이상과 기혼자에서 장점에 대한 인식 점수가 유의하게 낮았다. 전자상거래에서 식품 구매자는 비구매자보다 '가공식품의 잦은 섭취', '달고 기름진 음식의 잦은 섭취', '외식', '과음 및 잦은 음주'의 식행동 점수가 낮아 바람직하지 않은 것으로 나타났다. 전자상거래에서 식품 구매비용이 높을수록 '우유 매일 섭취'의 식행동은 바람직한 반면, '가공식품의 잦은 섭취', '달고 기름진 음식의 잦은 섭취', '외식', '과음 및 잦은 음주'는 바람직하지 않은 것으로 나타났다. 전자상거래에서 식품 구매자는 비구매자보다 '천천히 여유롭게 식사', '편식하지 않고 음식을 골고루 섭취', '과식하지 않고 적당히 섭취' 점수가 낮아 바람직하지 않은 것으로 나타났으며, 식품 구매비용에 따라서는 금액이 낮을수록 '천천히 여유롭게 식사하는 편'의 식습관 점수가 높았다. 이상의 결과를 종합할 때 성인 여성의 87.6%가 전자상거래를 통한 식품 구매 경험을 가지고 있었으며, 전자상거래에서 식품 구매경험이 있거나 그 비용이 클수록 바람직하지 않은 식행동과 식습관을 보였다. 이와 같이 전자상거래에서 식품 구매는 소비자의 식행동 및 식습관과 관련성이 있는 것으로 나타나고 있기 때문에 지속적으로 증가하고 있는 전자상거래를 이용한 식품 구매 대상자들에게 건전한 식품구매와 올바른 식생활을 유도할 수 있는 지속적인 관심과 영양지도가 요구된다.